On the relationship between inflation rate and inflation uncertainty: an application of the GARCH family models - Mohd Nor, Abu Hassan Shaari; Tan, Yan Ling; Maarof, Fauziah (Penerbit Universiti Kebangsaan Malaysia, 2007)
The main objective of this paper is to explore the varying volatility dynamic of inflation rate in Malaysia for the period from January 1980 to December 2004. The GARCH, GARCH-Mean, EGARCH and EGARCH-Mean models are used to capture the stochastic variation and asymmetries in the economic instruments. Results show that the EGARCH model gives better estimates of sub-periods volatility. Further analysis using Granger causality test show that there is sufficient empirical evidence that higher inflation rate level will result in higher future inflation uncertainty and higher level of inflation uncertainty will lead to lower future inflation rate.